PENGGUNAAN PUZZLE SEBAGAI MEDIA INOVATIF DALAM PEMBELAJARAN IPS SD KELAS III - Ardi Purwa Nugraha; Wahyu Purwiyastuti; Listyani Listyani (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2025)
Abstract. Social Studies lessons for grade three at Satya Wacana Christian Laboratory Elementary School still used the leaturing method or telling method. In another context, the lecturing method is considered less innovative. However, through this research it was found that social studies knowledge, teachers and students were open to the use of puzzles as an innovative tool in understanding elementary social studies material with the theme “Stories from my Hometown”. Puzzle with picture symbols of sports figures from Salatiga city were effective for students to practice when understanding the characters and characteristics in their immediate environment. This research used qualitative methods to obtain data. The research was also conducted using ethnographic methodology to read the classroom culture. The results showed that the use of puzzle media in the social studies learning process in class IIIB of Satya Wacana Christian Elementary School successfully showed its benefits to provide enthusiasm in receiving knowledge and creating critical behavior of students at the elementary school level. Social studies teachers using innovative methods in the form of puzzles results in positive results in the learning process. Students are motivated after learning social studies using visual media in the form of pictures of sports figures from Salatiga city. Students are also inspired to prepare themselves to become important and successful figures in the future so that they can have an impact on introducing the culture of their city to the world. Based on this reflection,   it can be concluded that puzzles are useful for bringing innovation to social studies learning in elementary schools.